Low Reynolds number effect on CFD prediction of bio inspired aerodynamics - Boughoue, Smail; Omar, Ashraf A.; Elsayed, Omer Ali; Boukharfan, Radouan; Mohammed Aldheeb, Mohammed Abdulmalek (American Institute of Aeronautics and Astronautics Inc, AIAA, 2022)
This work is motivated by the need for the implementation of the best numerical modelsfor low Reynolds flows and presents the state–of–the–art of the implemented models for thetransition of the laminar-turbulent predictions. The numerical models are applied to investigatethe aerodynamic characteristics and flow behavior around bird–like airfoils. Two DimensionalReynolds Averaged Navier Stokes (2D RANS) and Three-Dimensional Unsteady (3D U-RANS)methods are applied at a Reynolds number of105, whereas two-dimensional laminar simulationsand three-dimensional Large Eddy Simulation are employed for the known Owl-like airfoil atReynolds number of2.3×104. The numerical results of flow fields around Owl-like airfoil atthe latter Reynolds number using two-dimensional laminar and 3DLES predict correctly theunsteadiness of the aerodynamic coefficients. The 2D and 3D RANS methods are predicting wellthe aerodynamics characteristics for the man-made-bird-like airfoil at Reynolds number of105.